Proceedings of the 3rd International Conference on Education Innovation (ICEI 2019) 2019
DOI: 10.2991/icei-19.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adduction of Folding Paper Stages for Children’s Fine Motor Skills

Abstract: The purpose of this study is to illustrate the impact of giving folding stages to the subtle motoric abilities of children, especially in folding paper. The sample in this study was 15 children. Data collection techniques used observation, interviews, and documentation. The research observation sheet includes measuring the ability to fold a child, 3 namely: 1) the child is able to connect the a to b side symmetrically correctly, 2) the child is able to connect a side to b quickly and press it firmly, 3) the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It allowed us to form parameters for developing a model for organizing information cooperation that increases the quality of the educational process and improves the methodological foundations of delivering knowledge at a successful level that increases motivation to study various subjects and disciplines, as well as allowing us to create conditions to enhance personal behavior in the classroom and independent work in the in-depth study of subjects. In this work, personal requests of students were taken into account, which were highlighted during the study, and which were laid as dominant in determining the effectiveness of the educational process and the formation of a student's cultural personality when comparing with the analysis of psychological and pedagogical foundations (Widayati et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It allowed us to form parameters for developing a model for organizing information cooperation that increases the quality of the educational process and improves the methodological foundations of delivering knowledge at a successful level that increases motivation to study various subjects and disciplines, as well as allowing us to create conditions to enhance personal behavior in the classroom and independent work in the in-depth study of subjects. In this work, personal requests of students were taken into account, which were highlighted during the study, and which were laid as dominant in determining the effectiveness of the educational process and the formation of a student's cultural personality when comparing with the analysis of psychological and pedagogical foundations (Widayati et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…PFA is a kind of integrated learning experience requiring young children to systematically and strategically apply their mathematic and fine motor skills; thus, it has been widely regarded as a kind of art and craft activity in the early childhood classroom. However, its potential contribution to the early development of spatial skills has not been thoroughly explored (Dinehart and Manfra, 2013;Imaroonrak et al, 2018;Widayati et al, 2019). A recent study found that paper folding skills were highly correlated with spatial ability (SA) (Taylor and Hutton, 2013), indicating that there might be a predictive relationship between them.…”
Section: Folding Paper As a Mediator Of Spatial Skillsmentioning
confidence: 99%
“…However, in the early childhood context, PFA has been widely regarded as a learning activity to develop young children's fine motor skills and the sense of artistry (Dinehart and Manfra, 2013;Zhao, 2015;Nishida, 2019). The existing studies have widely explored its educational values on early arts and motor skills: (1) as an art education, PFA has been implemented in Japanese kindergartens for over 140 years, serving as a kind of symbolic art and craft culture (Nishida, 2019); (2) as an indicator of fine motor skills, PFA has been used to measure young children's fine motor skills (Dinehart and Manfra, 2013;Vidoni et al, 2014;Saraiva et al, 2019); and (3) as training of visual-motor integration, PFA has been proved to significantly improve the creativity and visualmotor integration (Imaroonrak et al, 2018;Widayati et al, 2019) in young children.…”
Section: Pfa In Early Educational Contextsmentioning
confidence: 99%